Capitalizing on cosmopolitanism in the Gulf - Koch, Natalie (Current history, 2019)
In the emirates where noncitizens comprise most of the population, states have made a show of welcoming outsiders - up to a point. Third in a series on ways of governing.
Keywords: Golfstaaten